Rapid Visible Light-Driven Water Disinfection with CTAB-Modified UiO-66-NH 2 - Li, Haibei; Chen, Mengqiu; Zhao, Yue; Zhang, Tangping; Li, Xinmei; Chen, Tianjiao; Zhou, Shuqing; Shi, Danyang; Yang, Zhongwei; Yang, Dong; Li, Junwen; Jin, Min (Environmental science & technology, 2025)
Water is the most essential resource for life, hence ensuring its universal availability in a rapid and reliable manner is highly desirable. Visible light-based catalytic disinfection is gaining prominence due to its accessibility and exceptional energy efficiency. In this study, we demonstrated that cetyltrimethylammonium bromide (CTAB)-modified UiO-66-NH (CTAB@UiO-66-NH ) effectively harnesses visible light to achieve highly efficient water disinfection. Introducing CTAB into these nanosystems reduced the charge-transfer resistance and facilitated charge separation, enabling efficient generation of reactive oxygen species and ultimately enhancing photocatalytic activity. CTAB@UiO-66-NH demonstrated outstanding water disinfection, achieving approximately 6-7 log inactivation of a broad spectrum of bacteria within 20 min under simulated visible light. It also exhibited stable cyclic disinfection performance and good biocompatibility, highlighting broad application prospects. Furthermore, CTAB@UiO-66-NH showed promising disinfection performance in real river water, achieving a 2.5 log colony-forming unit reduction of bacteria in Haihe River samples within 20 min of visible light irradiation. Therefore, our study offers a simple and affordable path to rapid access to safe water.